Visual perception in alpine ski racing. A qualitative analysis based on interviews with top-level athletes - Schläppi, O.; Urfer, J.; Kredel, R. (Sportwissenschaft, 2016)
Background. Alpine ski racing involves extreme conditions regarding speed, forces, and shuddering slopes. Contrary to other sports, the nature of visual perception in ski racing has hardly been explored. Consequently, focused interviews were conducted to gather information on the role of visual perception in alpine skiing and to identify relevant issues for future research. Methods. Twenty members of the Swiss national team were interviewed using a semi-structured interview guide focusing on athletes` gaze behavior, factors affecting visual perception, and strategies to cope with perceptual difficulties. Subsequently, verbal data were analyzed by inductive content analysis according to Mayring to generate categories based on the interviewmaterial itself, instead of forcing data into existing theoretical frameworks. Results. The athletes underlined the importance of visual perception for optimal performance. Even though they seem to rather unconsciously pick up visual information during races, general performance-related gaze strategies and visual cues could be identified. As factors affecting visual perception quality, perturbations, visibility, physical condition, alertness, time pressure, andmental condition were reported. On the athletes` side, these factors are faced by strategies referring to race preparation, gaze behavior, or skiing technique. Finally, the analysis highlighted the fact that, in the eyes of the athletes, expertise in alpine skiing is determined by a strong mutual interdependency of perception and action. Conclusion. Our findings provide several starting points for future empirical research. In this regard, apart from gaze-related issues, interactions between visual perception and motor performance, e.g., for the optimization of handling perturbations, seem to be of particular interest.